Crime and intelligence analysis: an integrated real-time approach - Grana, Glenn (CRC Press, 2017)
Part I. Crime and the twenty-first century -- Part II. Law enforcement : then and now -- Part III. Intelligence and intelligence analysis -- Part IV. Crime analysis -- Part V. Crime analysis and the future.